Chosen risk factors for osteoporosis and the level of knowledge about the disease in peri- and postmenopausal women - Janiszewska, Mariola; Kulik, Teresa; Dziedzic, Małgorzata A.; Żołnierczuk-Kieliszek, Dorota (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction : Osteoporosis as a chronic disease, affecting especially women in postmenopausal age, is an important, social and economic health problem especially of women of today’s world. The aim of the study was to assess the level of knowledge of women in the peri- and postmenopausal period about the prevention of osteoporosis and show the influence of chosen risk factors on the level of this knowledge. Material and methods : A group of 300 women aged 45-65, being patients of healthcare centres in Chełm, Lublin and Zamość (Lublin voivodeship, south-eastern Poland) were included in the study. The purposive sampling was used. Osteoporosis Knowledge Test (OKT) 2011 was the research tool. Gathered material was subjected to descriptive and statistical analysis. Tukey’s test, t-student test and variance analysis (ANOVA) were all applied. An accepted p materiality level was < 0.05 and p < 0.01. Results : Respondents presented the average level of knowledge about the role of physical activity in the prevention of osteoporosis (M = 13.93) and a low level of knowledge about well-balanced diet rich in calcium (M = 9.77). The knowledge about risk factors, screening and treatment remained on the average level (M = 8.00). An influence of socio-demographic factors on the level of knowledge was shown. Also some behaviours, associated with the lifestyle indeed influenced the level of this knowledge. Conclusions : Professional educational programs on osteoporosis should be implemented in the population of Polish peri- and postmenopausal women.